Enhanced Seismic Imaging of Complex Geological Structures Using Model-Constrained Kirchhoff Pre-Stack Depth Migration: Numerical Validation and Field Application - Lei Wang; Shengjian Wang; Lei Zhang; Xianhua Hou (Applied Sciences, 2025)
Seismic imaging in areas with complex geological structures, such as steeply dipping strata and lateral velocity variations, remains a significant challenge in geophysical exploration. In this paper, a Kirchhoff pre-stack depth and pre-stack time migration imaging method under the constraint of an initial model is proposed. By establishing the initial velocity model, the method is iteratively optimized under the horizon constraint, and the travel time difference is used to update the model. Finally, Kirchhoff pre-stack imaging is realized. Numerical simulations using a synthetic five-layer velocity model demonstrate that removing direct wave interference and incorporating horizon constraints significantly improve the signal-to-noise ratio and structural accuracy of the migration results. A field case study in a coalfield with monoclinic structures and high-angle faults further validates the method’s effectiveness. Comparative analysis with pre-stack time migration reveals that Kirchhoff pre-stack depth migration achieves superior fault delineation, diffraction wave homing, and event continuity, particularly in steeply dipping formations. The results highlight the method’s potential for improving seismic interpretation accuracy in complex structural settings, offering practical value for coal mine safety and resource exploration.